NMR SPECTROSCOPY OF PHASE TRANSITIONS IN MINERALS - Phillips B.L. (My University, 2000)
Nuclear magnetic resonance (NMR) spectroscopy has been used extensively since the 1960’s to study phase transformations. When Lippmaa et al. (1980) presented the first significant high-resolution solid-state NMR spectroscopic study of minerals, the study of structural phase transitions by NMR was a mature field, appearing primarily in the physics literature (e.g., Blinc 1981; Rigamonti 1984). The sensitivity of NMR spectroscopy to short-range structure (first- and second-coordination spheres) and low-frequency dynamics (i.e., frequencies much lower than the thermal vibrations of atoms) make it useful for determining changes in the structure and dynamics of solids that occur near phase transitions. This combination of characteristic time- and distance-scales is not easily accessible by other techniques. Widely studied phase transformations include order-disorder and displacive transitions in compounds with perovskite, antifluorite, β-K2SO4 (A2BX4), KH2PO4 (“KDP”), and other structure types, including some mineral phases (e.g., colemanite; Theveneau and Papon 1976). These studies used primarily single-crystal techniques and were mostly limited to phases that exhibit high symmetry and possess one crystallographic site for the nucleus studied. In some cases, the NMR data can help distinguish order-disorder from purely displacive transition mechanisms. Also, careful measurement of NMR relaxation rates provides information on the spectral density at low frequencies, which reflects softening lattice vibrations or freezing-in of rotational disorder modes. Many phase transitions interesting to mineralogists became accessible to NMR spectroscopy in the late 1980’s with the commercial availability of magic-angle-spinning (MAS) NMR probe assemblies capable of operation at extended temperatures (up to about 600°C) and the development of high-temperature NMR capability at Stanford (Stebbins 1995b). These technical advances enabled many of the structural transitions that occur in minerals to be studied in situ by NMR, including those in phases for which large single crystals are not available. MAS-NMR …